1965
DOI: 10.1524/zkri.1965.122.3-4.185
|View full text |Cite
|
Sign up to set email alerts
|

Beziehungen zwischen den Strukturen der Modifikationen des Platin- und Kupferphthalocyanins und einiger Chlorderivate*

Abstract: The instable modifications a I and all (previously called y) of copper phthalocyanine are isomorphous with the stable modifications a I of 4-monochloro-copper phthalocyanine, and a of platinum phthalocyanine respectively. The latter two can be obtained as single crystals and we have determined the essential structural features of them. By isomorphy considerations it was possible to recognize the structural differences between the 8, a I and all modifications of copper phthalocyanine.These a-structures are very… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(13 citation statements)
references
References 0 publications
2
11
0
Order By: Relevance
“…When deposited on a flat surface, it was directly seen by optical microscopy that the needles have the habit of lying nearly parallel to that surface, with their long axes randomly oriented in the plane. From powder x-ray diffraction data, 7 the structure could be classified as ␣I form, 8 and from the cell dimensions it was concluded that the molecules are stacked parallel to each other along the short b axis at intervals of 3.78 Å, and the molecular planes are inclined at an angle of 26.5°with respect to the ac plane, 7 in good agreement with the previous x-ray data. 9 The temperature dependent Mössbauer measurements have been performed using a helium bath cryostat between 4.2 K and room temperature.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…When deposited on a flat surface, it was directly seen by optical microscopy that the needles have the habit of lying nearly parallel to that surface, with their long axes randomly oriented in the plane. From powder x-ray diffraction data, 7 the structure could be classified as ␣I form, 8 and from the cell dimensions it was concluded that the molecules are stacked parallel to each other along the short b axis at intervals of 3.78 Å, and the molecular planes are inclined at an angle of 26.5°with respect to the ac plane, 7 in good agreement with the previous x-ray data. 9 The temperature dependent Mössbauer measurements have been performed using a helium bath cryostat between 4.2 K and room temperature.…”
Section: Methodssupporting
confidence: 82%
“…There are several types of phases, depending on the angle and the shift along the crystallographic b axis of one linear chain with respect to the other. 8 In particular, FePc crystallizes in the ␣ ͑Ref. 9͒ and ␤ ͑Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A plot of D 2 n as a function of n (see figure 12) gives a straight line from which values of 16.8 Å for D 0 and 26.4 Å 3 for V m can be calculated. The value of D 0 found in this study is consistent with the diameter of 13.9 Å calculated for unsubstituted Pc from X-ray studies [37] and the value of 17 Å estimated for D 0 from CPK models. Although rotation of the whole molecule around the normal to the molecular plane and fluctuations of this axis around the core direction might be possible in the mesophase, this agreement implies that in the mesophase the plane of the Pc nucleus is on average perpendicular to the column axis.…”
Section: Structuresupporting
confidence: 90%
“…Subsequently the crystal structures o f p-metalfree [ 2 ] , 0-nickel [3] and platinum phthalocyanine 141 were reported. At a later stage Honigmann, Lennk and Schrodel [5] showed that a-and ycopper phthalocyanine were isomorphous with 4-monochloro-copper phthalocyanine and platinum phthalocyanine, respectively, and by comparing the structures of the latter were able to recognize the structural differences between a-, pand ycopper phthalocyanines.…”
Section: Introductionmentioning
confidence: 99%